Tracking of gross motor coordination in Portuguese children - Henrique, Rafael S. (2017)
The purpose of this study was to investigate the tracking of gross motor coordination (GMC) and to profile children at 6 years of age who consistently showed higher stability patterns in different levels of GMC. The participants were 245 children (123 boys and 122 girls) who were assessed longitudinally from 6 to 9 years of age. GMC was assessed using the Korperkoordinationtest fur Kinder (KTK) test battery. Anthropometry, physical activity, and health- and performance-related physical fitness were also measured. Cohen’s kappa (κ) was used to estimate tracking. Tracking was poor for all GMC tests (0.17 ≤ κ ≤ 0.38) and moderate for the GMC motor quotient (MQ) in both boys and girls (0.44 ≤ κ ≤ 0.45). Instability at the extremes was low in GMC tests and negligible for MQ. Children who consistently showed high GMC levels during the 4 years of follow-up were lighter, had lower body mass index and subcutaneous fat, and showed higher scores in physical fitness tests at 6 years of age than those who consistently had low GMC levels. In conclusion, GMC showed low-to-moderate tracking over time in childhood. However, children who consistently demonstrated high GMC levels over time had healthier profiles at 6 years of age.